Type II diabetes mellitus self-management: relating diabetes distress, social support, self-efficacy, and performance of diabetes self-care activities - Dawson, Christine, author; Malcolm, Matthew, advisor; Atler, Karen, committee member; Williford, Anne, committee member (Colorado State University. Libraries, 2020)
Type 2 Diabetes Mellitus (T2DM) is a widespread chronic disease that negatively impacts an individual's health and well-being, particularly when uncontrolled. Due to the nature of T2DM, individuals are responsible for the challenge of self-managing the disease. Several factors act as barriers and facilitators to self-management, but the literature has failed to establish consensus about how these factors interact with one another. The present study utilized a correlational design to examine the relationships among diabetes distress, social support, self-efficacy, and performance of diabetes self-care activities. A total of 33 adults with T2DM participated in the study by completing a battery of surveys regarding performance of diabetes self-care activities and psychosocial factors. Self-efficacy was associated with diabetes distress (ρ = -.419). Support satisfaction was related to both self-efficacy (ρ = .495) and diabetes distress (ρ = -.431), although relationships were not found with other aspects of social support. We did not find any significant relationships among the psychosocial variables and performance of diabetes self-care activities, though both psychosocial factors and performance of diabetes self-care activities were linked to key health indicators like A1C and BMI. Our findings suggest that these psychosocial factors should be areas of interest for healthcare practitioners, researchers, and individuals with T2DM. Diabetes distress, self-efficacy, and social support should be assessed and monitored, in addition to performance of diabetes self-care activities. Future research should continue to explore relationships among psychosocial and contextual factors and their potential impact on ability to successfully self-manage T2DM.
Keywords: type 2 diabetes mellitus; diabetes self-management